Analysis the Effect of Money Ethics and Tax Morale on Tax Evasion With Lifestyle as a Moderation Variabel - Angella Keristiani Tia; Djunita Permata Indah (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
This study aims to determine the effect of money ethics and tax morals on tax evasion with lifestyle as a moderating variable. This study uses a quantitative approach with purposive sampling as a sampling technique. The questionnaire was distributed electronically to 130 taxpayers who live in West Kalimantan, especially Pontianak city. Statistical testing using Statistical Product and Service Solutions (SPSS), shows the results that tax morals and money ethics have a positive and significant effect on tax evasion. Lifestyle as a moderating variable is also able to strengthen the influence of tax morals and money ethics on tax evasion. Based on the T-test result with the results of money ethics = 0.001, tax morals = 0.000 and lifestyle = 0.034, which is less than 0.5, thus indicating that H0 is rejected, meaning that money ethics, tax morals and lifestyle also have a significant influence on tax evasion. The implications of this research are expected to be useful, especially for the government so that the government can prevent companies from committing tax evasion.